2010
DOI: 10.1002/ddr.20372
|View full text |Cite
|
Sign up to set email alerts
|

Peoniflorin prevents the adhesion between inflammatory endothelial cells and leukocytes through inhibiting the activation of MAPKs and NF‐κB

Abstract: The vascular endothelium can be activated by multiple factors, including lipopolysaccharide (LPS) functioning as a key component of the inflammatory response. Activated endothelium promotes the recruitment of leukocytes mainly by releasing various adhesion molecules and amplifies inflammation via a feedback loop. Peoniflorin, the main active constituent of the roots of Paeonia lactiora Pall., possesses anti-inammatory, anti-infective, and anti-platelet aggregative properties. To elucidate the anti-inammatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, our previous study , together with the study by Xu et al (2010), has indicated the antiinflammatory effects of PF in endothelial cells, namely by blocking adhesion molecules and chemokine production. Moreover, endothelial inflammation and oxidative stress are vital in the pathogenesis of various vascular diseases, such as cutaneous vasculitis.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, our previous study , together with the study by Xu et al (2010), has indicated the antiinflammatory effects of PF in endothelial cells, namely by blocking adhesion molecules and chemokine production. Moreover, endothelial inflammation and oxidative stress are vital in the pathogenesis of various vascular diseases, such as cutaneous vasculitis.…”
Section: Discussionmentioning
confidence: 94%
“…PF pretreatment could suppress MPO activity in lung tissues. Considering that leukocyte-endothelial interaction is essential for PMN recruitment to lung tissues, our previous findings that PF could prevent the adhesion of inflammatory endothelial cells to different kinds of leukocytes may provide a plausible explanation for PF attenuating the infiltration of PMNs [13]. Furthermore, disruption of vascular barrier integrity will lead to increased permeability of fluid and respiratory failure [28].…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin (PF), the major active constituent of TGP, has been reported to have many pharmacological effects, such as antiallergic [7], antiarthritic [8], hepatoprotective [9], and analgesic [10]. Recently, it was documented to be able to inhibit the properties systemic inflammatory responses in cecal ligation and puncture-induced sepsis [11], a main reason for ALI, protect against lipopolysaccharide (LPS)-induced liver inflammation, and prevent the adhesion between LPS-induced inflammatory endothelial cells and leukocytes [12,13]. Furthermore, it was proven to exhibit inhibitory effects on neuroinflammation, and analgesic effects through activating adenosine A1 receptor [14,15], which is beneficial for reducing PMN cell trafficking and microvascular permeability in LPS-induced lung injury [3].…”
Section: Introductionmentioning
confidence: 99%
“…Not coincidentally, Xu et al. ( 99 ) found that paeoniflorin significantly down-regulated E-selectin expression at the gene and protein levels. Paeoniflorin also inhibited the phosphorylation of JNK and p38 in a dose dependent manner, thereby suppressed the MAPK signaling pathway.…”
Section: The Detailed Mechanism Of Action Of Paeoniflorin In Combatin...mentioning
confidence: 99%